Reactive power sharing in microgrid using virtual voltage - Eder A. Molina-Viloria; John E. Candelo Becerra; Fredy E. Hoyos Velasco (International Journal of Electrical and Computer Engineering (IJECE), 2021)
The traditional droop control strategy has been applied previously in microgrids (MGs) to share accurately the active power. However, in some cases the result obtained when sharing reactive power is not the best, because of the parameters related to the distances from distributed generators (DGs) to the loads and the power variations. Therefore, this paper proposes a reactive power control strategy for a low voltage MG, where the unequal impedance related to the distances between generators and loads requires adjustments to work with the conventional frequency and voltage droop methods. Thus, an additional coefficient is calculated from parameters of the network that relate the location of elements. The test is perfomed by simulations in the MATLAB-Simulink software, considering a three-node MG with three DGs and a load that can change power at different periods of time. The results show that it is possible to improve reactive power sharing between the DGs located in the MG according to the load changes simulated and to improve voltages with this method.